Construction of an optical fiber filter - Afiq Ammarul Ezzuddin Shamsudin (2019)
This final year report will be examining efforts in constructing an optical fiber filter specific to hollow-core fibers (HCF). It involves the exploration of the effects of heating on changing the HCF fiber structure to potentially change its operational wavelength region. The initial part of the paper presents several different experiments conducted to explore heating effects on the HCFs, from which a constant issue arose: the microhole collapse effect of the HCF’s mini capillaries that run through the fiber length. Afterward, a pressurized experimental heating procedure was theorized to have potential in mitigating the issue from which the full construction of the pressure apparatus was ensued and documented, followed by a series of hands-on experiments to determine if pressurized heating could potentially help in resolving the collapse of holes problem in HCFs. The second portion of the experiments also included several computations in order to compare a before and after of the processed HCF fibers in order to determine if the pressurized method did influence the fiber’s structural parameters.